Evaluation of Retinoids for Induction of the Redundant Gene ABCD2 as an Alternative Treatment Option in X-Linked Adrenoleukodystrophy - Weber, Franziska D. (Public Library of Science, 2014)
X-linked adrenoleukodystrophy (X-ALD), the most common peroxisomal disorder, is a clinically heterogeneous disease that can manifest as devastating inflammatory cerebral demyelination (CALD) leading to death of affected males. Currently, the only curative treatment is allogeneic hematopoietic stem cell transplantation (HSCT). However, HSCT is only effective when performed at an early stage because the inflammation may progress for eighteen months after HSCT. Thus, alternative treatment options able to immediately halt the progression are urgently needed. X-ALD is caused by mutations in the ABCD1 gene, encoding the peroxisomal membrane protein ABCD1, resulting in impaired very long-chain fatty acid metabolism. The related ABCD2 protein is able to functionally compensate for ABCD1-deficiency both in vitro and in vivo. Recently, we demonstrated that of the cell types derived from CD34(+) stem cells, predominantly monocytes but not lymphocytes are metabolically impaired in X-ALD. As ABCD2 is virtually not expressed in these cells, we hypothesize that a pharmacological up-regulation of ABCD2 should compensate metabolically and halt the inflammation in CALD. Retinoids are anti-inflammatory compounds known to act on ABCD2. Here, we investigated the capacity of selected retinoids for ABCD2 induction in human monocytes/macrophages. In THP-1 cells, 13-cis-retinoic acid reached the highest, fivefold, increase in ABCD2 expression. To test the efficacy of retinoids in vivo, we analyzed ABCD2 mRNA levels in blood cells isolated from acne patients receiving 13-cis-retinoic acid therapy. In treated acne patients, ABCD2 mRNA levels were comparable to pre-treatment levels in monocytes and lymphocytes. Nevertheless, when primary monocytes were in vitro differentiated into macrophages and treated with 13-cis-retinoic acid, we observed a fourfold induction of ABCD2. However, the level of ABCD2 induction obtained by retinoids alone is probably not of therapeutic relevance for X-ALD. In conclusion, our results suggest a change in promoter accessibility during macrophage differentiation allowing induction of ABCD2 by retinoids.